FORMATION OF THE ORGANIZATIONAL AND MANAGEMENT COMPETENCE OF THE PROSPECTIVE TEACHERS-DEFECTOLOGISTS - Сергеєва, Валентина (SWorldJournal, 2023)
The article highlights the topical issue of the formation of organizational and management competence of future special education teachers, particularly those majoring in Defectology. The organizational and managerial competence of a defectology specialis